2022
DOI: 10.1111/adj.12899
|View full text |Cite
|
Sign up to set email alerts
|

The quality and readability of online molar incisor hypomineralization patient education materials: a systematic analysis

Abstract: Background Molar incisor hypomineralization (MIH) is estimated to affect 14% of children worldwide. It is crucial that patients and their families have access to easily comprehensible and reliable MIH‐relevant information. This study aims to determine the quality, reliability and readability of online patient education materials about MIH. Methods A systematic search strategy was adopted. Five validated tools were used to assess the content of the 21 websites that satisfied inclusion/exclusion criteria. Data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(97 reference statements)
1
5
0
1
Order By: Relevance
“…This complexity could be attributed to terminology and scientific language, mainly since around 40% of the evaluated websites are affiliated with universities or medical centers. Our findings align with studies conducted on medical health-related patient materials [ 14 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This complexity could be attributed to terminology and scientific language, mainly since around 40% of the evaluated websites are affiliated with universities or medical centers. Our findings align with studies conducted on medical health-related patient materials [ 14 , 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…The National Institutes of Health (NIH) suggests writing patients' health information in a language that individuals can easily understand in grades six to seven [ 14 ]. Our research found that the average FRES, CLI, FKGL and SMOG scores were 42, 12, 11.7, and 10.5, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may make it more difficult for users with a lower level of knowledge and literacy to understand and process the content. Some previous studies also rated the readability of online health information on Ankyloglossia [73], posttraumatic stress disorder [74], syndactyly release [75], and molar incisor hypo-mineralization [76] as difficult. It should be noted that websites that are more readable but lack credibility, pose a threat to readers because people usually tend to seek websites that are simple to understand.…”
Section: Discussionmentioning
confidence: 99%
“…Reliability is evaluated by DISCERN and JAMA. Eight studies examined reliability (Aldairy et al, 2012;Ang et al, 2022;Bojrab 2nd et al, 2020;Meade & Dreyer, 2022;C. B. Patel et al, 2022;Sideris et al, 2021;Spiers et al, 2017;Vargas et al, 2017;Wallace et al, 2005).…”
Section: Reliabilitymentioning
confidence: 99%
“…C. Lee et al, 2019;Lim et al, 2021;Langbecker & Janda, 2012;Lipari et al, 2019;Liu et al, 2014;Louw et al, 2013;Luk et al, 2010;Luk & Aslani, 2011;Mac et al, 2020;Macdonald et al, 2010;Magrath et al, 2022;Manchaiah et al, 2020;Mani et al, 2021;Martin et al, 2022;McBride et al, 2017;McEnteggart et al, 2015;Meade & Dreyer, 2022;Mehta et al, 2018;Miguens-Vila et al, 2018;Mikhail et al, 2015;Miles et al, 2020;Miles et al, 2021;Mira et al, 2013;Murphy et al, Pearson et al, 2022;Phillips et al, 2015;Piredda et al, 2016;Pires & Cavaco, 2014;Pothier et al, 2008;Powell et al, 2021;Prabhu et al, 2016;Prieto et al, 2020;Protheroe et al, 2015;Raeis, 2006;Rai et al, 2021;Rayess et al, 2017;Redfern et al, 2006;Rhee et al, 2013;Robb et al, 2019;Robinson & Schumacher, 2013;Rooney et al, 2020;Rosenberg et al, 2016;…”
Section: Acknowledgementsunclassified